Copyright issues faced by libraries in the time of corona: An insight into the position under Malaysian Copyright Law - Cheng Peng, Sik (Malaysian Journal of Library and Information Science, 2020)
The COVID-19 outbreak has brought substantial disruption to life and many sectors at one stroke. The pandemic has forced the closure of many schools and universities across the world. With teaching and learning activities being shifted to an entirely online environment, libraries too, undergo dramatic changes in the way they deliver and supply materials. Libraries may meet the need and request for resources when people stay or work at home by either scanning the physical books in their collections, or to make available e-Books to a greater number of users. Nonetheless, the said two acts may trigger copyright issues. This research aims to explore the copyright challenges encountered by libraries when engaged in the said activities and seeks to suggest the possible approaches to be pursued by libraries in doing so. This research employs the doctrinal research methodology, the typical methodology for legal research. With the findings of this research, it is hoped that this paper may clear the air on the copyright concerns faced by libraries during the pandemic. In addition, the paper also strives to offer guidance to the libraries in Malaysia as to how they may perform their role during a virus outbreak without infringing copyright.